2017
DOI: 10.1177/0310057x1704500206
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Cell-Based Coagulation Model in the Management of Critical Bleeding

Abstract: The cell-based coagulation model was proposed 15 years ago, yet has not been applied commonly in the management of critical bleeding. Nevertheless, this alternative model may better explain the physiological basis of current coagulation management during critical bleeding. In this article we describe the limitations of the traditional coagulation protein cascade and standard coagulation tests, and explain the potential advantages of applying the cell-based model in current coagulation management strategies. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 84 publications
0
18
0
2
Order By: Relevance
“…With this caveat in mind, viscoelastic tests can be considered as a useful adjunct to clinical judgment to stratify a patient's risk of developing thromboembolism, in addition to its more established role of guiding blood product transfusion in critical bleeding. 14,63 F I G U R E 4 The funnel plot, with the regression line in dashed line (P = .879), shows no obvious publication bias. ESS, effective sample size.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…With this caveat in mind, viscoelastic tests can be considered as a useful adjunct to clinical judgment to stratify a patient's risk of developing thromboembolism, in addition to its more established role of guiding blood product transfusion in critical bleeding. 14,63 F I G U R E 4 The funnel plot, with the regression line in dashed line (P = .879), shows no obvious publication bias. ESS, effective sample size.…”
Section: Discussionmentioning
confidence: 96%
“…First, evidence suggests that whole-blood viscoelastic tests have the potential to inform the clinicians about the mechanisms of bleeding over and above the information provided by standard coagulation blood tests. 14,63 Because a viscoelastic test assesses the clotting process of whole blood, including platelets, it has a potential to reflect bleeding or thrombotic tendency that is not measurable by activated partial thromboplastin time or prothrombin time, as both tests only use platelet-poor plasma. 63 Our results suggested that a viscoelastic hypercoagulable state is associated with an increased risk of thromboembolism, a 3.6-fold higher odd, compared to those without a hypercoagulable state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La cascada de coagulación de manera tradicional se explica en base a dos vías: la intrínseca y la extrínseca; ambas confluyen en una vía común. En la actualidad se ha puesto en entredicho el modelo clásico de la coagulación, apareciendo el llamado "modelo celular" 71 , en el que cobra importancia considerar a las propias células como elementos esenciales en el proceso de coagulación.…”
Section: Coagulaciónunclassified
“…Even though many patients with major trauma will have deranged coagulation profiles which are considered as contraindicated to receive anticoagulant prophylaxis, their propensity to develop VTE does not appear to be different from those without such acquired coagulopathy. [59][60][61] This group of patients with trauma will serve as the best candidates to assess the cost-effectiveness of IVC filters and will form the study population of this planned RCT in which we will adopt a proactive approach to detect VTE in our study patients (for details see below).…”
Section: Introductionmentioning
confidence: 99%